MCGM installed location marker - Ghosh, Ayan (2023)
Banganga Tank is located on the western fringes of Malabar Hill, close to Raj Bhawan. The neighborhood around Banganga Tank is the oldest continuously inhabited region in Bombay, a site of great spiritual significance to Hindus. For centuries, the Walkeshwar Temple and the now destroyed Shri Gundi stone at Malabar Point gave sanctity to the hill from a very early age and remains a site where devotees still throng.